Connecting the dots: a versatile model for the atmospheres of tidally locked Super-Earths. Issue 1 (8th October 2014) - Carone, L.; Keppens, R.; Decin, L.
Abstract : Radiative equilibrium temperatures are calculated for the troposphere of a tidally locked Super-Earth based on a simple greenhouse model, using Solar system data as a guideline. These temperatures provide in combination with a Newtonian relaxation scheme thermal forcing for a 3D atmosphere model using the dynamical core of the Massachusetts Institute of Technology global circulation model. Our model is of the same conceptional simplicity than the model of Held & Suarez and is thus computationally fast. Furthermore, because of the coherent, general derivation of radiative equilibrium temperatures, our model is easily adaptable for different planets and atmospheric scenarios. As a case study relevant for Super-Earths, we investigate a Gl581g-like planet with Earth-like atmosphere and irradiation and present results for two representative rotation periods of P rot = 10 d and P rot = 36.5 d. Our results provide proof of concept and highlight interesting dynamical features for the rotating regime 3 < P rot < 100 d, which was shown by Edson et al. to be an intermediate regime between equatorial superrotation and divergence. We confirm that the P rot = 10 d case is more dominated by equatorial superrotation dynamics than the P rot = 36.5 d case, which shows diminishing influence of standing Rossby–Kelvin waves and increasing influence of divergence at the top of the atmosphere. We argue that this dynamical regime change relates to the increase in Rossby deformation radius, in agreement with previous studies. However, we also pay attention to other features that are not or only in partial agreement with other studies, like, e.g. the number of circulation cells and their strength, the role and extent of thermal inversion layers, and the details of heat transport.